Racial/ethnic differences in clinical trial enrollment, refusal rates, ineligibility, and reasons for decline among patients at sites in the National Cancer Institute's Community Cancer Centers Program - Aisha T. Langford; Ken Resnicow; Eileen Dimond; Andrea Denicoff; Diane St. Germain; Worta McCaskill‐Stevens; Rebecca A. Enos; Angela Carrigan; Kathy Wilkinson; Ronald S. Go (2013)
BACKGROUND This study examined racial/ethnic differences among patients in clinical trial (CT) enrollment, refusal rates, ineligibility, and desire to participate in research within the National Cancer Institute's Community Cancer Centers Program (NCCCP) Clinical Trial Screening and Accrual Log . METHODS Data from 4509 log entries were evaluated in this study. Four logistic regression models were run using physical/medical conditions , enrollment into a CT , patient eligible but declined a CT , and no desire to participate in research as dependent variables. RESULTS Age ≥ 65 years (OR = 1.51, 95% CI = 1.28‐1.79), males (OR = 2.28, 95% CI = 1.92‐2.71), and non‐Hispanic black race (OR = 1.53, 95% CI = 1.2‐1.96) were significantly associated with more physical/medical conditions . Age ≥ 65 years was significantly associated with lower CT enrollment (OR = 0.83, 95% CI = 0.7‐0.98). Males (OR = 0.78, 95% CI = 0.65‐0.94) and a higher grade level score for consent form readability (OR = 0.9, 95% CI = 0.83‐0.97) were significantly associated with lower refusal rates. Consent page length ≥ 20 was significantly associated with lower odds of “no desire to participate in research” among CT decliners (OR = 0.75, 95% CI = 0.58‐0.98). CONCLUSIONS There were no racial/ethnic differences in CT enrollment, refusal rates, or “no desire to participate in research” as the reason given for CT refusal. Higher odds of physical/medical conditions were associated with older age, males, and non‐Hispanic blacks. Better management of physical/medical conditions before and during treatment may increase the pool of eligible patients for CTs. Future work should examine the role of comorbidities, sex, age, and consent form characteristics on CT participation. Cancer 2014;120:877–884 . © 2013 American Cancer Society .